RANCANG BANGUN PROGRAM APLIKASI SISTEM PAKAR UNTUK DIAGNOSIS HAMA UTAMA KEDELAIUNTUK DIAGNOSIS HAMA UTAMA KEDELAI - Roja, Atman (Informatika Pertanian, 2012)
Pest infestation to soybean plant results in yield losses up to 80%. Therefore, it needs to be controlled properly. The main problem in controlling it is that far mers a nd ext ension workers a re difficult to promptly diagnose the types of main pest infecting the plant in the field. In consequence to the technology applied to control it is not appropriate. Whether it is mechanically, biologically, and chemically. To help them in making prompt decission, a user friendly tool need to be developed. One of the tools is an expert system. The development and implementation of the system were carried out at Indonesian Assessmetn Institute for Agricultural Technology (IAIAT) of West Sumatera Province and Universitas Putra Indonesia, Padang. The project was conducted from March to September 2009. The methodology applied in designing, developing, and implementing. The system was process-oriented methodology that is a model driven technique orienting to a process. The expert system generated uses based knowledge of 15 pests types attaching soybean plant, 7 sites of plant damage, 53 damage symptoms, and 166 nules. While the knowledge base is 15 technologies of main pest management having certainty factor/CF around 0.8 â€“ 1.0. The system interface consists of two forms, that are one for advanced user and the another one for farmer or extension worker. The advanced one is able to improve the existing knowledge as well as the rules and the non advanced just consult to the system. The developed system need to be further developed to make it comprehensive. The system is also called â€œSipakar Hatmalaiâ€.